Defining the Maturity Levels for Implementing Industrial Logistics Practices in Construction - Tetik, Müge; Peltokorpi, Antti; Seppänen, Olli; Holmström, Jan (Frontiers in Built Environment, 2022)
Logistics practices are processes that require alignment and coordination among project actors to support successful construction operations. While recent research has underlined the effects of material logistics solutions on project performance, such as productivity and waste, no single best practice for logistics solutions currently exists. Therefore, practitioners need more knowledge on development paths toward successful logistics solutions. To address this gap, we seek to define the different maturity levels of logistics practices in construction and then outline the development paths for project actors to progress from amateur to more advanced and industrial logistics solutions. Based on a review of current practices obtained from the literature, we propose the maturity levels of planning, organizing, operating, use of technology, and information flow regarding the logistics practices in construction. We devise a recommended order for implementing logistics practices and investigate how companies can advance their logistics maturity from one level to the next. The proposed model has been validated via case examples from the industry. The paper contributes to construction logistics research by describing how companies can navigate development efforts to gradually improve their logistics practices. Future research could conduct more case studies within different project contexts.